2010
DOI: 10.1063/1.3457219
|View full text |Cite
|
Sign up to set email alerts
|

Fe–Pd thin films as a model system for self-organized exchange coupled nanomagnets

Abstract: In equilibrium the Fe–Pd system on the iron rich side of the phase diagram demixes into Fe and L10-ordered FePd. Here, we examine the suitability of the demixing process for self-organized formation of exchange coupled thin film magnets. In this way the benefit of the high magnetization of Fe is combined with the high magnetocrystalline anisotropy of FePd. By using combinatorial methods the influence of composition and thickness on structure, microstructure, and magnetic properties is analyzed. Experiments sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…[15][16][17][18] A well-known problem raised recently is that the switching magnetic field is still too high for write applications due to the high anisotropy field caused by the large K. In order to ameliorate this condition, a composite of soft and hard magnetic materials is effective in reducing the switching field. 19,20 As a model case, we have recently reported the exchange-coupling magnetic property of the ␣-Fe/ L1 0 -FePd dual-phase region in the Fe-Pd alloy system, 21 and Schied et al 22 also reported recently the exchange-coupling behavior of this same system. The Fe-Pd alloy system is attractive in that the soft magnetic ␣-Fe and hard magnetic L1 0 -FePd coexist in thermal equilibrium.…”
Section: Introductionmentioning
confidence: 92%
“…[15][16][17][18] A well-known problem raised recently is that the switching magnetic field is still too high for write applications due to the high anisotropy field caused by the large K. In order to ameliorate this condition, a composite of soft and hard magnetic materials is effective in reducing the switching field. 19,20 As a model case, we have recently reported the exchange-coupling magnetic property of the ␣-Fe/ L1 0 -FePd dual-phase region in the Fe-Pd alloy system, 21 and Schied et al 22 also reported recently the exchange-coupling behavior of this same system. The Fe-Pd alloy system is attractive in that the soft magnetic ␣-Fe and hard magnetic L1 0 -FePd coexist in thermal equilibrium.…”
Section: Introductionmentioning
confidence: 92%
“…The FePd alloy is promising candidate for Bit Patterned Media technology due to its strong perpendicular magnetic anisotropy. [7] However, this feature appears only in alloys with L1 0 structure, epitaxial or polycrystalline with strong (001) texture. [8] The tetragonal L1 0 structure with the alternating planes of Fe and Pd atoms is the anisotropic crystal with strong magnetocrystalline anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…The development of new materials for the magnetic storage industry requires investigation of the new methods of their fabrication. Magnetic thin alloy films with L1 0 crystal structure such as FePd, FePt and CoPt, which exhibit a large uniaxial magnetic anisotropy of a few MJ/m 3 , [1][2][3][4] are considered as potential materials for the bit pattern high-density recording media with information density over 1 Tbit/in 2 . Application of these materials in data storage devices with perpendicular recording requires the fabrication of (001)textured film.…”
Section: Introductionmentioning
confidence: 99%